2021
DOI: 10.3389/fneur.2020.595038
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of a 2D Volume-Referencing Endolymphatic-Hydrops Grading System With Extra-Tympanic Electrocochleography in Patients With Definite Ménière's Disease

Abstract: Background: Although magnetic resonance imaging (MRI) of the membranous labyrinth and electrocochleography (ECochG) have been used to diagnose endolymphatic hydrops (ELH) in patients with Ménière's disease (MD), the relationship between imaging and ECochG is not well-documented.Objectives: This study evaluates the ELH using 3D-FLAIR MRI and extra-tympanic ECochG (ET-ECochG) and correlates the results from 3D-FLAIR MRI to those from ET-ECochG.Materials and Methods: 3D-FLAIR MRI images of 50 patients were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…FIGURE 3 | EH grading in three parts of the inner ear and the sum of VR scores. EH in cochlea were scored 0, 3, 6, and 9 for four grades while those in vestibule were scored 0, 4, 8, and 12 and those in the semicircular canals as 0, 5, 10, and 16 according to the volume-referencing scores (12). The sum score of three parts represented EH in the entire inner ear.…”
Section: Eh Evaluation and Mri Association With Clinical Characteristicsmentioning
confidence: 99%
“…FIGURE 3 | EH grading in three parts of the inner ear and the sum of VR scores. EH in cochlea were scored 0, 3, 6, and 9 for four grades while those in vestibule were scored 0, 4, 8, and 12 and those in the semicircular canals as 0, 5, 10, and 16 according to the volume-referencing scores (12). The sum score of three parts represented EH in the entire inner ear.…”
Section: Eh Evaluation and Mri Association With Clinical Characteristicsmentioning
confidence: 99%
“…Furthermore, the significance of EH and vestibular function tests in patients with MD has not been fully characterized yet. The recent research published by our team modified the grading system of vestibular and semicircular canal hydrops (15). The "volume-referencing" grading system showed a better correlation with the MD clinical features and had more diagnostic value than previously published methods.…”
Section: Discussionmentioning
confidence: 97%
“…The scan parameters for the 3D-FLAIR sequence were as follows: time of repetition = 6,500 ms, time of echo = 286.1 ms, time of inversion = 1,950 ms, flip angle = 67 • , slice thickness = 0.6 mm, echo train length = 160, field of view = 200 * 200 mm, and matrix size = 256 * 256, voxel size = 0.78 * 0.78 * 1.1 mm. The scan time was 6 min 11 s. Three dimensional heavily T2weighted spectral attenuated inversion recovery (3D-T2-SPAIR) sequence was also performed with the following parameters: voxel size = 0.65 * 0.52 * 0.76 mm, scan time = 4 min 30 s, TR = 1,300 ms, TE = 254.7 ms, flip angle = 110 • , slice thickness = 0.4 mm, field of view = 200 * 200 mm, and matrix size = 384 * 384 (15).…”
Section: Intratympanic Gd Injection and Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…A more detailed clinical study and discussion can be found in another work (76). To date, correlations were found for SQ grades 3-point [electrocochleography (EcochG)(83,84)] and 4-point ordinal cochlear scale [PTA…”
mentioning
confidence: 99%